Curative therapy for rectal cancer. Issue 2 (1st February 2021) - Alawawdeh, Anas; Krishnan, Tharani; Roy, Amitesh; Karapetis, Christos; Joshi, Rohit; Singhal, Nimit; Price, Timothy
ABSTRACT: Introduction : A comprehensive trimodality approach has become the standard of care for patients with locally advanced rectal cancer. However, the sequencing and duration of chemotherapy and chemoradiotherapy around surgery varies between clinical studies and geographical regions. Growing evidence is also mounting for strategies such as total neoadjuvant therapy and non-operative management for carefully selected patients. Areas covered : We provide a perspective review of the current evidence and controversies in the treatment of locally advanced rectal cancer including the recent updates from the 2020 ASCO annual conference. Expert opinion : With ongoing advances in the management of locally advanced rectal cancer, a multidisciplinary team approach is necessary as treatments could involve multiple approaches. Chemoradiotherapy whether short or long course followed by at least 3 months of systemic chemotherapy may be the preferred option to balance local and distant disease control. Albeit the choice of doublet or triplet chemotherapy is still controversial. As total neoadjuvant treatment becomes part of the standard of care in rectal cancer, modification of the surveillance schedule is needed to detect early recurrences which may be limited by resources and availability of services.